EFFECTIVENESS TEST OF OIL PALM LEAF EXTRACT (Elaeis guineensis Jacq.) AS A MOSQUITO BIOLARVACIDE Aedes aegypti - Setiawan, Deni; Hadi, Samsul; Shindi, Muhammad Riki; Mahdi, Nur; Rinda, Ririn Purnama (Jurnal Farmasi Sains dan Praktis, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease that is transmitted by female mosquito species Aedes aegypti which has spread all over the world. Efforts to control the Aedes aegypti mosquito vector by using natural biolarvicides using oil palm leaf extract. The purpose of this study was to determine the effectiveness of oil palm leaf extract (Elaeis guineensis Jacq.) as a biolarvicide for the Aedes aegypti mosquito. This study employs 600 Aedes aegypti larvae in an experimental post-test only control group design. Concentrations of oil palm leaf extract (OPLE) ranging from 1000 to 4000 ppm, using temephos as a positive control and aquadest as a negative control. The mortality of Aedes aegypti larvae was calculated every 1 hour during the 48-hour observation period. SPSS was used to analyse data to determine the concentrations of LC90 and LT50. The results of this study indicate the probit analysis value (LC90) of Aedes aegypti larvae is 2190 ppm with time (LT50) the fastest concentration of killing 4000 ppm with a time of 37,183 hours. Based on the results of research, oil palm leaf extract (Elaeis guineensis Jacq.) has a biolarvicidal effect on the larvae of the third instar Aedes aegypti mosquito.